Lama Fermentasi Feses Ternak Babi Menggunakan Biogas Mini Terhadap Volume Gas bio Dan Lama Nyala Api - Nautus Stivano Dalle (Jambura Journal of Animal Science, 2022)
The purpose of this study is to determine the effect of biogas fermentation on biogas volume and flame duration. This study used the feces of peranakanduroc pigs with an age of 1.5 years. The design used is a complete randomized design with a direct experimental method. The treatment tried was P0: Fermentation of pig feces for 6 days; Q1: Fermentation of pig feces for 12 days; Q2: Fermentation of pig feces for 18 days; Q3: Fermentation of feces of pig herds for 24 days. The variables studied are the calculation of the diameter of the digester, the calculation of the volume of gas and the flame test. The results of statistical analysis used descriptive analysis and resulted in an unreal effect on the research variable (P0.05), but there was an increase in gas volume and flame tests based on treatment so that it can be concluded that the longer the fermentation time, the biogas volume will also increase